P7.09 CORRELATION BETWEEN THE CENTRAL AND BRACHIAL BLOOD PRESSURE AND ASYMPTOMATIC CAROTID ATHEROSCLEROSIS - R. Böcskei; B. Benczúr; A. Cziráki; F. Molnár; M. Illyés (Artery Research, 2009)
Last year we presented that PWVao is a significant marker of early atherosclerosis. Now we were interested about how could the comparison of the central and brachial blood pressure predict the early atherosclerosis. The aim of this study was to analyze the relation between the central and brachial blood pressure and the asymptomatic, subclinical carotis atherosclerosis, and to determine the sensitivity and the specificity of the two BP measurements. Method: 499 asymptomatic subjects were included in this study. Central and brachial blood pressure were measured simultaneously with oscillometric method (Arteriograph) and carotid scan was performed with carotid ultrasonography in both side by a “blinded” investigator. Results: Cases when higher central BP was measured than on the brachial, were regarded as abnormal. According to this classification χ2 test showed that significantly more atherosclerotic cases were present in the abnormal BP class. Sensitivity and specificity values were found to be moderate: 59.2 (95% CI 52.8–65.3) and 63.5 (95% CI 57.6–69.1), respectively, as well as the positive and negative predictive values: 58.7 (95% CI 52.3–64.8) and 64.0 (95% CI 58.1–69.6). However, odds ratio showed promising result: 2.53 (95% CI 1.76–3.63). Conclusion: It seems that the difference between central and brachial BP can be a predictor of atherosclerosis in asymptomatic subjects, and is worth to measure.